The social impact of cultivated and plant-based meats as radical innovations in the food chain: Views from Brazil, the United States and Europe - Morais-da-Silva, Rodrigo Luiz; Reis, Germano Glufke; Sanctorum, Hermes; Molento, Carla Forte Maiolino (Frontiers in Sustainable Food Systems, 2022)
Cultivated and plant-based meats have been recognized as radical innovations that may revolutionize food production worldwide. Despite potentially being more sustainable than conventional meat, little is known about the consequences these innovations can bring to society. To help to clarify this topic, we studied the social impacts that cultivated and plant-based meats may bring to Brazil, the United States and Europe. Based on the perspective of 136 experts, our results are divided into market expectations, consumer access, consumer acceptance, impacts on farms, and business opportunities along the new chains. Experts generally predicted an optimistic picture of the social effects with several opportunities as alternative meats become available. However, the consequences for animal farmers seemed worrying in the experts' views. Overall, the opinion of Brazilian and American experts seemed more optimistic than that of Europeans. Our findings may be helpful for practitioners and people involved in rural policy interested in better guiding this transition process in the food production chain.